Eric J. Hobsbawm e a Era do Socialismo : da Revolução Russa ao colapso da União Soviética (1917-1991) - Santos, Antonio Carlos dos (2011)
The present work rescues the reflections of the English marxist historian Eric Hobsbawm about the history of the socialism within the Brief XX Century , more specifically the soviet socialism between the year 1917, in Russia, and the collapse of the Soviet Union, in 1991. Beginning from his personal history as a communist activist and as an intellectual of the English Social History we outline his ideas about the socioeconomic and political conditions which originated the October of 1917 and the raise of the so called really existing socialism in the Soviet Union and East Europe, as well as its implications on the history of the XX century, on marxist thinking, and on the political strategies of the international communist movement. Using tools as the ontological conception of the marxist work identified initially by György Lukács and kept on by István Mészáros and José Chasin we tried to analyse the contribution of Hobsbawm s historiographical thinking on the fight to overcome inequalities economic and social injustices created by the hegemonic capitalist mode in the world nowadays